Thus Spoke Ahuramazda: 2004: A Systemcide -on To –the-l.m.d. Odyssey - Nacif Labed (The Journal of Studies in Language, Culture and Society, 2024)
The reform brought about in the tertiary tuition some years ago certainly had a wellintentioned aim of a transformation for better. The decision-maker behind such a reform pushed by a dire need of reform instead of taking us on an enthralling pedagogic voyage led us rather in the dire straits, on a odyssey of which Odysseus, Homerus‟ hero, could ne envious! Ever since the 2004 systemcide of the Classical System to the present day, the imperious problems of that new system have become standing out conspicuously! The return safely to our pedagogic Ithaca, we directly need an Ahumazda, a kind of lord of light and wisdom to lead us out of that rampant malarkey.